2001
DOI: 10.1093/jac/48.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Prototype trial design for rapid dose selection of antiretroviral drugs: an example using emtricitabine (Coviracil)

Abstract: Antiretroviral monotherapy for initial drug characterization risks the selection of resistant virus, yet monotherapy is the only setting where many fundamental properties of a new drug can be reliably determined. Using data on viral replication kinetics and dynamics, we designed an accelerated (14 day) open-label study of single agent emtricitabine (formerly known as FTC)--a nucleoside reverse transcriptase inhibitor--to select a dosing regimen for further therapeutic study. Five regimens (25 mg bd, 100 mg od,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 6 publications
2
33
1
Order By: Relevance
“…However, only 0.1% of patients with moderate renal impairment had a daily AUC lower than the threshold of maximal anti-HIV activity (10 mg · h/liter). As FTC is a well-tolerated drug, even at higher dosing levels (300 mg QD [19] or 200 mg twice a day (BID) [20]), an increase in FTC exposure for patients with moderate renal impairment receiving 200 mg QD is not expected to have major effects on the safety profile of FTC.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 0.1% of patients with moderate renal impairment had a daily AUC lower than the threshold of maximal anti-HIV activity (10 mg · h/liter). As FTC is a well-tolerated drug, even at higher dosing levels (300 mg QD [19] or 200 mg twice a day (BID) [20]), an increase in FTC exposure for patients with moderate renal impairment receiving 200 mg QD is not expected to have major effects on the safety profile of FTC.…”
Section: Discussionmentioning
confidence: 99%
“…The second objective was to measure the active intracellular metabolites of FTC in neonates, as previously high intracellular phosphorylated metabolites for lamivudine triphosphate (3TC-TP) and zidovudine triphosphate (AZT-TP) during the first 2 weeks of life have been detected (7). Few data have been reported so far on FTC-TP in adults (14,17), and there are, to our knowledge, no data from neonates. In the present study, FTC-TP concentrations were measured in peripheral blood mononuclear cells (PBMCs) extracted from the cord and from neonatal plasma and compared to adult concentrations.…”
mentioning
confidence: 99%
“…However, viral breakthrough is detected in approximately 16% to 32% of patients after 1 year of treatment (12). Newer oral nucleoside/nucleotide analogues in clinical trials, such as adefovir dipivoxil (4), entecavir (6), and emtricitabine (19,18), appear to be at least as potent as lamivudine. In vitro and in vivo studies showed that adefovir and entecavir are also effective in suppressing lamivudine-resistant HBV (8).…”
mentioning
confidence: 99%